MULTIPLE TRANSLATIONS OF SUNDANESE FOLKLORE, NYI ROROKIDUL - Zulkifli Mahmud, Erlina; Sobarna, Cece; Moriyama, Mikihiro (Metahumaniora, 2024)
This article discusses multiple translations of Sundanese folklore, The Legend of Nyi Rorokidul from the Sundanese language as the source text into Indonesian as the first target text and English as the second target text. The background of this research involves two problems: there is still limited research dealing with multiple translations as well as the research about the translation of Sundanese folklore into English seen from internet search. The data source of this research is a book of a collection of Sundanese folklore consisting of Sundanese text as the source text, Indonesian as the first target text, and English as the second target text. The translation of the Sundanese folklore in the book also involves several foreign languages among others are Arabic, and Russian with the form that the foreign language text is given at the beginning of the book, and Indonesian is in the middle, then Sundanese language is at the final part. The book used for this research is entitled The Most Popular Sundanese Folklore: Myth, Legend, and Tales with Indonesian as the first target text and English as the second target text. By using descriptive-qualitative methods, this research aims to answer two questions: (i) What methods of translation are identified in the multiple translations of Sundanese folklore, Nyi Rorokidul; (ii) are the methods of translation identified in the first target text, Indonesian, and the second target text, English, the same? The results show that the methods of translation in the multiple translations of Sundanese folklore, Nyi Rorokidul involved literal translation, adaptation, free translation and communicative translation. Some parts of the source text are translated using the same methods in both target text and the rest is translated using a different method.